Myzostoma seymourcollegiorum n.sp. (Myzostomida) from southern Australia, with a description of its larval development - Rouse, Greg W.; Grygier, Mark J. (Zootaxa, 2005)
Few Myzostomida have been recorded from southern Australian waters. Most myzostome taxa to date have been described from the warmer waters of the Indo-Pacific, where their crinoid echinoderm hosts are most diverse. In this paper a new myzostome, Myzostoma seymourcollegiorum n. sp., is described from the crinoid Cenolia trichoptera (Comasteridae) taken from Encounter Bay near Adelaide, South Australia; further records suggest its range extends also to Tasmania and around eastern Australia to central New South Wales. Myzostoma seymourcollegiorum n. sp. is an ectocommensal on C. trichoptera and C. glebosus and there has previously been no myzostome recorded from any species of Cenolia. The new species resembles a number of other Myzostoma species that are quite flat and have a nearly circular shape with 20 short marginal cirri. The early stages of its larval development are also outlined and compared with those of other Myzostomida.